Hydrogel-Based Continuum Soft Robots - Honghong Wang; Jingli Du; Yi Mao (Gels)
This paper comprehensively reviews the latest advances in hydrogel-based continuum soft robots. Hydrogels exhibit exceptional flexibility and adaptability compared to traditional robots reliant on rigid structures, making them ideal as biomimetic robotic skins and platforms for constructing highly accurate, real-time responsive sensory interfaces. The article systematically summarizes recent research developments across several key dimensions, including application domains, fabrication methods, actuator technologies, and sensing mechanisms. From an application perspective, developments span healthcare, manufacturing, and agriculture. Regarding fabrication techniques, the paper extensively explores crosslinking methods, additive manufacturing, microfluidics, and other related processes. Additionally, the article categorizes and thoroughly discusses various hydrogel-based actuators responsive to solute/solvent variations, pH, chemical reactions, temperature, light, magnetic fields, electric fields, hydraulic/electro-osmotic stimuli, and humidity. It also details the strategies for designing and implementing diverse sensors, including strain, pressure, humidity, conductive, magnetic, thermal, gas, optical, and multimodal sensors. Finally, the paper offers an in-depth discussion of the prospective applications of hydrogel-based continuum soft robots, particularly emphasizing their potential in medical and industrial fields. Concluding remarks include a forward-looking outlook highlighting future challenges and promising research directions.